Status of the Fish Fauna of Ambazari Reservoir: A Relook after 90 Years - Swapnil S. Ghatge; Sachin W. Belsare; Shrikant S. Jadhav (Journal of Indian Fisheries Association, 2018)
The freshwater fish fauna of the Ambazari lake was studied for fish diversity. A total of 41 species of freshwater fish belonging to 7 orders and 15 families were recorded. After the ninety years of first study by D'Abreu (1925), authors would like to add new records of 19 fish species for Ambazari lake. Among these 19 species, 3 are transplanted species, 7 are exotic species and 9 native species. Of the 31 species reported by DAbreu (1925), authors could not record 9 species. The Anguilla bengalensis which is a near threatened species according to IUCN, could not be recorded from the lake. The fish fauna of Ambazari lake is threatened due to transplantation of exotic species and pollution in the lake.